Bedtime stories and book reports : connecting parent involvement and family literacy - Compton-Lilly, Catherine; Greene, Stuart (New York : Teachers College Press, 2011)
This book brings together the newest research on parent involvement and family literacy and asks this question: How do race, class, gender, and history serve as potent factors that shape children's school experiences?--[book cover]
Flipping the script: honoring and supporting parent involvement / Stuart Greene and Joyce F. Long ; A response to chapter 1 / Catherine Compton-Lilly -- Parents defining parent involvement / Patricia Snell ; A response to chapter 2 / Catherine Compton-Lilly -- Transformative change: parent involvement as a process of identity development / Joyce F. Long ; A response to chapter 3 / Catherine Compton-Lilly -- Parent involvement with a propose: get the lead out! / Rebecca Rodgers and Darren O'Brien ; A response to chapter 4 / Catherine Compton-Lilly -- Reading attainment over time: following urban families / Catherine Compton-Lilly ; A response to chapter 5 / Stuart Greene -- Intergenerational meaning-making between a mother and son in digital spaces / Tisha Y. Lewis ; A response to chapter 6 / Stuart Greene -- Talking, reading, and writing about lesbian and gay families in classrooms: the consequences of different pedagogical approaches / Caitlin L. Ryan ; A response to chapter 7 / Stuart Greene -- God's people are strong: children's spiritual literacy practices / Nadjwa E.L. Norton ; A response to chapter 8 / Stuart Greene -- Descubriendo historias/uncovering stories: the literary worlds of Latino children and families / Rosario Ordo{u4BA5}z-Jasis and Susana Y. Flores ; A response to chapter 9 / Stuart Greene -- Conclusions: connecting parent involvement and family literacy / Catherine Compton-Lilly and Stuart Greene.
Includes bibliographical references and index.
Keywords: Education -- Parent participation; Home and school; Parent-teacher relationships